2013
DOI: 10.5812/ircmj.3597
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of 8 weeks Aerobic and Yoga Training on Ambulatory Function, Fatigue and Mood Status in MS Patients

Abstract: BackgroundMultiple Sclerosis (MS) is a disease of the central nervous system that results in many symptoms including mobility limitation and fatigue.Patients and MethodsThirty-one MS patients, all female with mean of age of 36.75 years and Expanded Disability Status Scale scores (EDSS) of 1.0 to 4.0 were recruited. Subjects were randomly assigned to one of the three groups: treadmill training, yoga or control groups. Treadmill training and yoga practice consisted of 8 weeks (24 sessions, thrice weekly). The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
110
0
5

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(122 citation statements)
references
References 23 publications
7
110
0
5
Order By: Relevance
“…tent with the findings of Guner and Inanici, 42 whereas Ahmadi et al 34,35 reported no change in walking speed after yoga. The present pilot study found improved fatigue (postintervention) after yoga.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…tent with the findings of Guner and Inanici, 42 whereas Ahmadi et al 34,35 reported no change in walking speed after yoga. The present pilot study found improved fatigue (postintervention) after yoga.…”
Section: Discussionsupporting
confidence: 75%
“…Walking endurance improved statistically but did not achieve a clinically significant improvement in the present trial. Findings related to walking endurance in other studies are conflicting, with two studies reporting improvement in the 2-minute walk test distance 34,35 and two reporting no change in 6MWT distance. 37,38 The present finding of improved walking speed (T25FW) was consis-publicly available, we have not yet solicited feedback on its utility.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations